Deploying AI for New Product Development Success: By embracing and incorporating AI in all stages of NPD, companies can increase their success rate of NPD projects. Issue 5 (17th July 2021) - Zhang, Haili; Zhang,, Xiaotang; Song, Michael
Abstract : Overview: Organizations are rapidly adopting artificial intelligence (AI) to solve business problems, yet they are only beginning to harness its benefits. Published literature lacks empirical evidence regarding the value of deploying AI for innovation success. This study investigates how and where to deploy AI in the new product development (NPD) process. We present three lessons learned and three best practices for successful deployment of AI technologies for NPD success.